THE DYNAMICS OF USING THE MOBILE CONTROL RAPID REPORTING SYSTEM APPLICATION (SIPACE TROLLING) AT THE CLASS IIA MADIUN YOUTH CORRECTIONAL INSTITUTION - Hutapea, Uchox Alvyanus (Universitas Nusa Cendana, 2025)
Adopting technology in digital security systems requires adequate skills and knowledge for security management to achieve its objectives, which are to create conducive conditions, maintain officer order, and ensure prison safety. This research aims to ensure that organizations can identify, measure, and monitor the various risks that may arise from the application. This research uses a qualitative method with a descriptive approach by conducting in-depth interviews with correctional officers at the Class IIA Madiun Youth Correctional Institution who serve as structural and executive officials. From the risk identification, the results obtained from the four risk points that have been described can be an important concern for the organization in operating the application. From those with a high-risk value to those with the lowest risk value, all must get risk treatment because risks can interfere with the organization's running if the organization is not handled properly. Keywords: Application; Risk Management; Prison